Determinants of Circumcision Timing in Indonesia: A Mixed-Methods Study of Health, Cultural, and Socioeconomic Factors - Alwafi, Haris; Purnomo, Boyke Rudy; Wicaksono, Kristoforus Resi; Safitri, Lale Yomi (Jurnal Kesehatan Vokasional, 2026)
Background: Circumcision is widely practiced in Indonesia, yet its timing varies across regions despite known medical and economic advantages of early (neonatal) circumcision.Objective: This study aims to analyze the distribution and determinants of circumcision age in Indonesia using a mixed-methods approach, integrating quantitative data and qualitative insights.Methods: Data were collected from multiple circumcision providers across several provinces. Quantitative analysis was conducted to assess age distribution, while qualitative interviews explored parental decision-making. Findings were interpreted using the Health Belief Model and Social Ecological Model.Results: Most circumcisions occurred at ages 6–10 years, reflecting a dominant school-age pattern. Regional variation was observed, with earlier circumcision more common in West Nusa Tenggara and West Java, and delayed circumcision in Central Java and East Kalimantan. Decisions were influenced by cultural norms, religious beliefs, financial readiness, perceived pain, and social expectations. Economic factors also contributed, as delayed circumcision was often linked to financial planning and ceremonial practices, while early circumcision was perceived as more cost-efficient.Conclusion: Circumcision timing in Indonesia is shaped by multi-level determinants beyond medical considerations. Culturally sensitive strategies are needed to promote informed decision-making.Keywords: Circumcision; Timing; Determinants